The Effect of Clark’s Angle and Body Weight on Dynamic Balance in School-Aged Children - Rizqi Nurul Inayah; Ketut Laksmi Puspa Dewi; Enny Wulandari; Edy Waspada (Griya Eka Sejahtera, 2026)
Background: Foot structure and body weight are considered important factors influencing dynamic balance in school-aged children. Dynamic balance in this study was assessed using the Functional Reach Test (FRT). This study aimed to analyze Effect of Clark’s Angle and Body Weight on Dynamic Balance in School-Aged Children.Methods: This study employed an analytical observational cross-sectional design. A total of 58 children aged 9–12 years were recruited using purposive sampling. The independent variables included Clark’s Angle of the left and right feet and body weight, while the dependent variable was dynamic balance measured using the FRT. Data analysis consisted of the Kolmogorov–Smirnov normality test and Pearson correlation analysis, with a significance level set at p < 0.05.Results: The findings revealed a very strong positive correlation between Clark’s Angle and FRT scores for both the right foot (r = 0.808) and the left foot (r = 0.801). In contrast, body weight demonstrated a significant negative correlation with FRT (r = –0.569). An almost perfect correlation between left and right Clark’s Angle values (r = 0.994) indicated a high degree of bilateral foot morphology symmetry within the sample. Children with higher medial longitudinal arches exhibited better dynamic balance, whereas those with flat feet or higher body weight tended to show reduced dynamic balance performance.Conclusion: Clark’s Angle is a significant predictor of dynamic balance in school-aged children, while increased body weight may adversely affect postural stability. Assessment of foot structure and body weight status should be incorporated into routine child health screening to support early intervention strategies aimed at improving motor development and balance.